Internationalization of Canadian Counselling Psychology: A Collaborative Endeavour Grounded in Social Justice - Sinacore, Ada L.; Huminuik, Kirby (Canadian Journal of Counselling and Psychotherapy, 2020)
During the Canadian Counselling Psychology Conference held at the University of Calgary in 2018, participants in a working group met to discuss the internationalization of counselling psychology and to articulate the ways in which the values of Canadian counselling psychology can inform international interactions. As an outcome of the working group process, the authors report on the themes that emerged: mapping the territory, movements and tensions, and challenges and opportunities. Taking these themes into consideration, the authors discuss the implications for researchers, educators, and clinicians in Canadian counselling psychology.